The Politics and Governance of Basic Education: A Tale of Two South African Provinces - Brian Levy; Robert Cameron; Ursula Hoadley; Vinothan Naidoo (Oxford University Press, 2018)
Uses cutting edge and multidisciplinary approaches to analyse the politics of service provision and serves as a model for how similar research can be conducted in other countries and sectors - An in-depth, microlevel analysis that develops the high-profile South African discourse on the interaction between governance and policy - Systematically anchored in innovative thinking on how to achieve gains in politically complex settings.
Keywords: 370; politics of service provision; South Africa; governance; policy